Implementation of Bandwidth Management Using Queue Tree at SMK Cipta Karya Bekasi - Solahudin Al Ayubih; Herman Kuswanto (Institute of Computer Science (IOCS), 2021)
Internet usage such as browsing information and downloading data at the Cipta Karya Vocational School in Bekasi City with the use of a computer lab, administrative office and teacher's room when used simultaneously, there is an inappropriate tug of war for bandwidth, so that the bandwidth allocation used is not optimal in its use, thus making administrative activities and teaching and learning activities are not going well, with the quality of service applied to bandwidth management this will make users use the internet to the maximum and there is no waste of bandwidth, then bandwidth management limits at SMK Cipta Karya Bekasi City are needed so that each part has a bandwidth of each so that there is no tug of war between the bandwidths, if used together, for its implementation, a Mikrotik router device is needed. By using a queue tree configuration on a proxy router with a queue tree configuration that can limit bandwidth by splitting each upload and download packet, the priority distribution can be more efficient in the selection of the packet. By using the queue tree configuration, the ideal bandwidth limit is applied at SMK Cipta Karya, Bekasi city.